Peran Roh Kudus dalam Mewujudkan Ecclesia Domestica dan Mencegah Oikia Meristhe di Jemaat GMIM Imanuel Toraget - Mumu, Andre Shevcenco; Poluan, Agnes Relly (PT. Giat Konseling Nusantara, 2026)
The Christian family is theologically understood as the Ecclesia Domestica (house church), an ideal